Innovation in local kuih: consumer’s behavioral intention towards Ready-Made Frozen Food (RMFF)/ Tengku Muaz Tengku Bahizalsah ... [et al.] - Tengku Bahizalsah, Tengku Muaz; Md Nor, Norfezah; Abdul Aziz, Saidatul Afzan; Ishak, Noriza (Universiti Teknologi Mara Selangor, 2022)
Local kuih based on ready-made frozen food (RMFF) product plays a significant role as a part of identity, culture, gastronomic legacy, and economic progress. Customer interest and preference may change over times. Due to this situation, the food industry entrepreneur must actively evolve with the innovation so they can retain or improve market share and profitability. However, this needs to correspond to the buyer preference. Therefore, this study investigated the antecedents that influence consumer behavioural intention towards purchasing local kuih ready-made frozen food (RMFF). In this study, an extended Theory of Planned Behavior (TPB) with modification was used. A quantitative esurvey was distributed through google form platform and was distributed to Penang residence in Malaysia. From this e-survey, 152 responses were received. Only 140 of the respondent’s data were valid. The data from 140 Penang resident consumers were then analysed using a descriptive statistic, followed by correlation and multi regression using SPSS 21 version. From the collected data, majority of the respondents were female (54.6%) with 64.5% were between 20-29 years old. Respondents with single status recorded the highest with 58.2%. The data collected also showed that 24.8% of the respondents work in professional field with household income between RM2000-RM3000 (34.1%). All factors including attitude (r= 0.592, p= 0.000), subjective norms (r= 0.544, p= 0.000), perceived behavioural control (r= 0.677, p= 0.00) and innovation (r= 0.266, p= 0.001) have a positive significant relationship towards intention to buy local kuih ready-made frozen food (RMFF) among the respondents. These indicate 63% of all the factors were found to influence respondents towards intention to buy local kuih ready-made frozen food (RMFF). Hence, this may have a positive impact on Small Medium Enterprise (SME) who produce local kuih ready-made frozen food (RMFF) business while maintaining the authentic taste of the local delicacies.